2021
DOI: 10.3390/ma14227103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Furnace Slag and Coal Gangue Mixtures Stabilized by Cement and Fly Ash

Abstract: The mechanical properties and strength formation mechanism of cement–fly-ash-stabilized slag–coal gangue mixture were examined using an unconfined compressive strength test, splitting strength test, triaxial test, and scanning electron microscopy to solve the limitations of land occupation and environmental pollution that is caused by fly ash from the Xixia District thermal power plant in Yinchuan, slag from the Ningdong slag yard, and washed coal gangue. Its performance as a pavement base mixture on the road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, the amount of organic carbon depends on the time and temperature at which the municipal waste is incinerated. Sulfur, heavy metals, and chlorine depend on the chemical properties of the municipal waste [18].…”
Section: Bottom Ashmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the amount of organic carbon depends on the time and temperature at which the municipal waste is incinerated. Sulfur, heavy metals, and chlorine depend on the chemical properties of the municipal waste [18].…”
Section: Bottom Ashmentioning
confidence: 99%
“…Hence, the number of SCMs currently in use will decrease. Therefore, to fill the future market gap, substitutes such as 19 01 12 should be introduced, especially since the amount of waste is not decreasing despite the introduction of a waste hierarchy [18].…”
Section: Bottom Ashmentioning
confidence: 99%
“…As a basic building material, cement-and-fly-ash stabilized gravel (CFRCA) has been used in many construction applications, such as road bases, foundation reinforcement, and dam construction [ 1 , 2 , 3 , 4 ]. Studies have shown that CFRCA has a good carrying capacity and that if used as a road base, it has great potential in improving the structural carrying capacity of an asphalt pavement [ 5 , 6 , 7 , 8 ]. However, CFRCA is easily affected by environmental factors and is prone to shrinkage cracks in areas that undergo large differences in temperature and large differences in dry and wet conditions [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%